Development of an Android Based First Person Shooter Math Educational Game Application - Muhammad Maulidiy Sahli; Harya Bima Dirgantara (CV TOPAZART, 2023)
This study aims to develop an Android-based math education game with the Unity game engine as a learning medium for elementary school children. The formulation of the problem of this research is how to build an Android-based first-person shooter (FPS) math educational game as a learning medium for elementary school students. The researcher only took the material model that was applied to a limited game for the calculation model for the addition and subtraction of integers. The type of game used is a first-person shooter (FPS). The method used by the researcher is the Game Development Life Cycle (GDLC) method with stages: initiation, pre-production, production, game testing, beta, and release. The benefit of this research is to provide exciting and interactive alternative mathematics learning media. The final result of this research is an educational game entitled “Pistol Math” which can be played on Android devices. Based on user trial interviews with 20 respondents, 18 of 20 children became more interested and enthusiastic about learning with the learning method while playing the educational game “Pistol Math”.